Of a Storm in a Teacup and a Gutter Heater—Practical Aspects of VHP Room Fumigation. (September 2015) - Kümin, Daniel; Signer, Johanna; Portmann, Jasmine; Beuret, Christian
Room fumigation has traditionally been performed using formaldehyde. However, recently new methods have been developed, including vaporized hydrogen peroxide (VHP). VHP offers a number of advantages, such as degradation into non-toxic compounds (environmentally friendly), being non-corrosive (if used properly, with most common construction materials), leaving no residues, and being a vapor. On the other hand, it also poses new challenges in that the equipment is expensive (compared to formaldehyde), it has to be properly distributed inside the room, and fumigation cycles need to be developed for each room and situation. These challenges can be overcome as many laboratories have shown. In this article the authors outline the development of a VHP fumigation cycle and the validation of said cycle using the example of one laboratory at a new high-containment facility. Problems encountered as well as solutions that were or could have been implemented are also discussed. Even though the process was time-consuming and at times challenging, VHP room fumigation proved to be a versatile and robust process that may be used to efficiently decontaminate even complex laboratory setups.